2008
DOI: 10.1111/j.1547-5069.2008.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Nursing Surveillance on Hospital Cost

Abstract: The results of this study along with possible clinical benefits would indicate that frequent nursing surveillance is important and might support the need for additional nursing staff to deliver frequent surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…A total of 25 registered nurses and nurse managers participated in that study. Shever et al (2008) used the registry data (i.e., NIC) from 7,851 patient records at a tertiary hospital to calculate the cost of surveillance, and stated that without using a standardized nursing terminology this calculation would not be possible. The duration of the interventions measured in these observations was then used to calculate costs using unit values that indicate the relative effort of each intervention.…”
Section: Enable Calculation Of Resources Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 25 registered nurses and nurse managers participated in that study. Shever et al (2008) used the registry data (i.e., NIC) from 7,851 patient records at a tertiary hospital to calculate the cost of surveillance, and stated that without using a standardized nursing terminology this calculation would not be possible. The duration of the interventions measured in these observations was then used to calculate costs using unit values that indicate the relative effort of each intervention.…”
Section: Enable Calculation Of Resources Consumptionmentioning
confidence: 99%
“…The studies suggested that it is possible within the use of standardized codes, CCC (Dykes, Wantland, Whittenburg, Lipsitz, & Saba, 2013;Moss &Saba, 2011) andNIC (de Cordova et al, 2010), to measure or estimate the time taken to perform nursing interventions. Furthermore, it was found that it was possible to describe nursing care in electronic documentation systems inclusive of actions such as coordination of care and universal precautions (de Cordova et al, 2010;Dykes et al, 2013;Moss & Saba, 2011) and thereby calculate costs for nursing using NIC (Shever et al, 2008) and CCC (Dykes et al, 2013;Moss & Saba, 2011) (Table 2).…”
Section: Enable Calculation Of Resources Consumptionmentioning
confidence: 99%
“…Appropriate interventions can affect the hospital length of stay, costs, morbidity, mortality, and prevent potentially fatal outcomes for the neonatal population (Müller-Staub, Lavin, Needham, & van Achterberg, 2006;Shever et al, 2008;Stone & Gershon, 2009). Appropriate interventions can affect the hospital length of stay, costs, morbidity, mortality, and prevent potentially fatal outcomes for the neonatal population (Müller-Staub, Lavin, Needham, & van Achterberg, 2006;Shever et al, 2008;Stone & Gershon, 2009).…”
mentioning
confidence: 99%
“…How to dichotomize the treatment variable is the first decision the researcher makes in a propensity score analysis (see the bolded box at the top of Figure 1) and should be guided by clinical and empirical knowledge. The necessary steps for a propensity score analysis are shown in Figure 1 (Shever et al, 2008); this was influenced by a conceptual model developed for nursing effectiveness research (Titler, Dochterman, & Reed, 2004). …”
Section: Methodsmentioning
confidence: 99%